Detection of defects in adhesively bonded aluminium plates by digital speckle shearing interferometry - Lim, Lay Hua. (2008)
This dissertation describes the development of an experimental setup for the detection of surface and sub-surface defects in adhesively bonded aluminium plates using the technique of Digital Speckle Shearing Interferometry.